The extent to which the standards of the Commission for International Accreditation across regions (CITA) can be applied in leading schools in Jeddah from the perspective of leading school principals - Al-Sulami, Majed Atteah; Al-Subaihi, AbdulHayy Ahmed (Journal of Educational and Psychological Sciences, 2025)
The study aimed to determine the feasibility of applying the accreditation standards of the International Accreditation Agency Across Regions (Cognia) in leading schools in Jeddah from the perspective of their principals. The study adopted a purposive descriptive methodology, with a population consisting of 30 male principals of Cognia-accredited leading schools in Jeddah. The findings indicated that, overall, the application of accreditation standards in leading schools is highly feasible. Moreover, applying these standards significantly enhances the educational process. However, the challenges associated with implementing accreditation were also found to be significant. The study revealed statistically significant differences regarding the feasibility of applying Cognia accreditation standards in leading schools in Jeddah based on academic qualifications. However, no significant differences were found in the criterion of continuous educational improvement. Additionally, statistically significant differences were observed based on the school level, while no significant differences were found in leadership and organization. Furthermore, statistically significant differences were noted concerning the feasibility of applying Cognia accreditation standards in leading schools in Jeddah based on years of experience.